2004
DOI: 10.1002/hyp.1505
|View full text |Cite
|
Sign up to set email alerts
|

Suspended sediment concentration and the ripple–dune transition

Abstract: Abstract:Flume experiments were conducted in order to monitor changes in flow turbulence intensity and suspended sediment concentration at seven stages across the ripple-dune transition and at three different positions above the bed surface. Three-dimensional velocity measurements were obtained using an acoustic Doppler velocimeter (ADV). Suspended sediment concentration (SSC) was monitored indirectly using ADV signal amplitude. Although limited to timeaveraged parameters, the analysis reveals that SSC varies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
3
23
0
2
Order By: Relevance
“…The results indicate that the shape of the dunes have a major influence on the flow features, where as the effect of dune roughness is limited to the near wall region extending to a distance of about 80% of the dune height about the crest. Bennett and Best, (1996), Best (2005 a, b), Lopez et al, (2000), Robert and Uhlman (2001) and Schindler and Robert (2004) have shown that suspended sediment concentration increases with increase in scale and magnitude of turbulent structures. Schindler and Robert (2005) www.intechopen.com have concluded that the transition from 2-D to 3-D bed forms, result in increased sediment transport, increased turbulence and increased bed form migration rate.…”
Section: Effect Of Flow Depthmentioning
confidence: 98%
“…The results indicate that the shape of the dunes have a major influence on the flow features, where as the effect of dune roughness is limited to the near wall region extending to a distance of about 80% of the dune height about the crest. Bennett and Best, (1996), Best (2005 a, b), Lopez et al, (2000), Robert and Uhlman (2001) and Schindler and Robert (2004) have shown that suspended sediment concentration increases with increase in scale and magnitude of turbulent structures. Schindler and Robert (2005) www.intechopen.com have concluded that the transition from 2-D to 3-D bed forms, result in increased sediment transport, increased turbulence and increased bed form migration rate.…”
Section: Effect Of Flow Depthmentioning
confidence: 98%
“…The main objective of this section is to provide novel insights into the hydrodynamic processes that drive the complex morphological features we discussed in the previous section. Specifically, we seek to probe questions that have been at the centre of extensive debate in the literature, including, among other things: the linkage between coherent structures in the turbulent boundary layer and the initial bed instability (Colombini 2004;Venditti & Church 2005;Venditti et al 2006;Chou & Fringer 2010;Omidyeganeh & Piomelli 2013a,b), the role of flow separation off sand wave crestlines as a means for sand wave migration (Kostaschuk 2000;Schindler & Robert 2004;Best 2005;Colombini & Stocchino 2012) and the origin of low-frequency coherent structures rising to the water surface, also known as surface 'boils' (Jackson 1976;Yalin 1992;Venditti & Bennett 2000;Best 2005).…”
Section: Coupled Bed-flow Interactionsmentioning
confidence: 99%
“…As the ADV cannot distinguish between a phase difference of 1818 and À1798, the velocity recorded in the ADV file will change sign, producing a dramatic spike in the velocity data (Wahl, 2000). Aliasing may be generated when the effective distance to the boundary changes during sampling (Schlinder and Robert, 2004) or when there is interference from previous pulses reflected from boundaries with irregular profiles (Dey and Barbhuiya, 2005). In our experiments, aliasing occurred when fish were very close to the sampling volume.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 84%
“…Spikes, which will be eliminated, are those points outside of elliptical projection on the ellipsoid onto the three principal phase-space planes (uÀDu, DuÀD 2 u, uÀD 2 u). (3) Despiking filter has been used in different fields, such as in the study of turbulence in flumes (Biron et al, 2004;Schlinder and Robert, 2004;Dey and Barbhuiya, 2005;Scott et al, 2005) and in the measurement of turbulence in estuaries (Chanson et al, 2005). …”
Section: Data Post-processingmentioning
confidence: 99%